1999
DOI: 10.1002/(sici)1097-0215(19990105)80:1<98::aid-ijc19>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Protein-kinase-C? expression correlates with enhanced keratinocyte proliferation in normal and neoplastic mouse epidermis and in cell culture

Abstract: In order to gain insight into the biological function of a PKC iso‐enzyme, the protein kinase Cμ, we analyzed the expression pattern of this protein in mouse epidermis and keratinocytes in culture. Daily analysis of neonatal mouse epidermis immediately after birth showed a time‐dependent reduction in the PKCμ content. Expression of the proliferating‐cell nuclear antigen (PCNA), indicative of the proliferative state of cells, was reduced synchronously with PKCμ as the hyperplastic state of the neonatal tissue d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
28
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(36 citation statements)
references
References 23 publications
8
28
0
Order By: Relevance
“…The differential results obtained in this study with Gö6983, Gö6976, and bisindolylmaleimide I suggest that activation of PKC may be responsible for cell protection by IL-4. Recently, PKC expression was also found to be correlated with the proliferative state of murine keratinocytes and NIH3T3 fibroblasts (31). These results are also consistent with a recent study showing that inhibition of PKC with Gö6976 results in a significant increase of both caspase 3 and caspase 8 activity in anti-Fas-treated Jurkat cells (32).…”
Section: Discussionsupporting
confidence: 87%
“…The differential results obtained in this study with Gö6983, Gö6976, and bisindolylmaleimide I suggest that activation of PKC may be responsible for cell protection by IL-4. Recently, PKC expression was also found to be correlated with the proliferative state of murine keratinocytes and NIH3T3 fibroblasts (31). These results are also consistent with a recent study showing that inhibition of PKC with Gö6976 results in a significant increase of both caspase 3 and caspase 8 activity in anti-Fas-treated Jurkat cells (32).…”
Section: Discussionsupporting
confidence: 87%
“…Like calcium/calmodulin-dependent protein kinase II (Soderling, 1996), PKD also demonstrates an autophosphorylationmediated constitutive activity following its activation (Waldron et al, 1999). PKD activity increases with the addition of factors such as bombesin, vasopressin, and platelet-derived growth factor in Swiss 3T3 cells (Zugaza et al, 1997), and it has been shown that there is an increase in mitogenesis with PKD overexpression in fibroblasts (Rennecke et al, 1999;Zhukova et al, 2001). In addition, PKD levels are increased in cutaneous carcinomas and the proliferating compartment of mouse skin (Rennecke et al, 1999).…”
mentioning
confidence: 99%
“…PKD activity increases with the addition of factors such as bombesin, vasopressin, and platelet-derived growth factor in Swiss 3T3 cells (Zugaza et al, 1997), and it has been shown that there is an increase in mitogenesis with PKD overexpression in fibroblasts (Rennecke et al, 1999;Zhukova et al, 2001). In addition, PKD levels are increased in cutaneous carcinomas and the proliferating compartment of mouse skin (Rennecke et al, 1999). Thus, we hypothesized that PKD might play an antidifferentiative or proproliferative role in keratinocytes.…”
mentioning
confidence: 99%
“…Indeed, we have previously shown that Gö 6976, but not the other PKC inhibitors mentioned above, stimulates transglutaminase activity and enhances the effect of 1,25-dihydroxyvitamin D 3 in keratinocytes (Shapiro et al, 2002). Similarly, we (Shapiro et al, 2002) and others (Rennecke et al, 1999) have shown that Gö 6976, but not Gö 6983, inhibits DNA synthesis in keratinocytes as well. Furthermore, we have proposed that PKD serves as a proproliferative and/or antidifferentiative signaling enzyme in these cells (Shapiro et al, 2002; M. E. Dodd, V. L. Ristich, S. Ray, R. M. Lober, and W. B. Bollag, manuscript submitted for publication; for review, see Bollag et al, 2004).…”
Section: Discussionmentioning
confidence: 58%